2018
DOI: 10.1039/c8cp04595j
|View full text |Cite
|
Sign up to set email alerts
|

Cu(i) vs. Ru(ii) photosensitizers: elucidation of electron transfer processes within a series of structurally related complexes containing an extended π-system

Abstract: Heteroleptic Cu(i) complexes are a promising alternative towards traditional Ru(ii) photosensitizers. In particular, Cu(i) complexes of the type [Cu(P^P)(N^N)]+, where N^N represents a diimine and P^P a bulky diphosphine ligand, are already successfully applied for photocatalysis, organic light-emitting diodes or dye-sensitized solar cells. Therefore, this study aims for the systematic comparison of three novel heteroleptic Cu(i) compounds, composed of xantphos (xant) as P^P ligand and different diimine ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 107 publications
12
70
0
Order By: Relevance
“…420 nm, which is reminiscent to the absorption spectrum of an analogous reduced copper complex reported by Dietzek and coworkers. 70 However, these small changes in the UV spectra do not provide irrefutable evidence of a contribution from a reductive quenching pathway.…”
Section: Photocatalysismentioning
confidence: 95%
See 1 more Smart Citation
“…420 nm, which is reminiscent to the absorption spectrum of an analogous reduced copper complex reported by Dietzek and coworkers. 70 However, these small changes in the UV spectra do not provide irrefutable evidence of a contribution from a reductive quenching pathway.…”
Section: Photocatalysismentioning
confidence: 95%
“…S18b †). 70 Noting that 6 is itself photoactive under these conditions, we next investigated NEt 3 as a non-chromophore surrogate of 6, which possesses a similar E ox to 6 (E ox = 0.83 for NEt 3 , 71 E red = 0.82 V for 6). When NEt 3 is used as the quencher, only small absorption changes were found at ∼455 nm (Fig.…”
Section: Photocatalysismentioning
confidence: 99%
“…The analytical data agree with those published previously. 51,59,66,70,72 The properties of complex 1 are summarised in Table S1 in the ESI; † the absorption and emission spectra in acetonitrile solution, in the solid state, and when immobilised on silica, are shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…30,45,[49][50][51][52][53][54][55] Recent studies have shown that Cu(I) complexes containing one diimine ligand, and one diphosphine ligand such as 4,5-bis(diphenylphosphino)-9,9dimethyl-xanthine (xantphos), which has a large bite angle and high steric hindrance, can have even longer excited state lifetimes (ns-ms). [56][57][58][59][60] Cu(I) complexes are being increasingly used as photosensitisers in photocatalysis, 24,25,30,51,[61][62][63][64][65][66][67][68][69][70][71][72][73] and dyes-sensitised solar cells. 74 They are also used as antitumor [75][76][77][78] and antibacterial agents [79][80][81][82][83][84][85] due to their innate dark toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation